SidePoint: A Peripheral Knowledge Panel for Presentation Slide Authoring - Liu, Yefeng; Edge, Darren; Yatani, Koji (CHI 2013 Conference on Human Factors in Information Systems, 2013)
Presentation authoring is an important activity, but often requires the secondary task of collecting the information and media necessary for both slides and speech. Integration of implicit search and peripheral displays into presentation authoring tools may reduce the effort to satisfy not just active needs the author is aware of, but also latent needs that she is not aware of until she encounters content of perceived value. We develop SidePoint, a peripheral panel that supports presentation authoring by showing concise knowledge items relevant to the slide content. We study SidePoint as a technology probe to examine the benefits and issues associated with peripheral knowledge panels for presentation authoring. Our results show that peripheral knowledge panels have the potential to satisfy both types of needs in ways that transform presentation authoring for the better.